Stryhnos potatorum and Pisum sativum as natural coagulant for meat food processing wastewater treatment: isotherm studies - Pahazri, Nor Fadzilah; Mohd Apandi, Najeeha; Radin Mohamed, Radin Maya Saphira; Nagarajah, Ramathasan; Mohd Apandid, Affah; Mohd Radzuan, Rosmawanie; S. Moganathan, Shamine (Taylor&francis, 2023)
This study was to determine the flocculation performance of Stryhnos Potatorum (Nirmali seed) and Pisum Sativum (pea seed) as natural coagulants for treating meat food processing wastewater (MFPW). A lab-scale treatment tank was developed to evaluate the effectiveness of MFPW treatment.The flocculation process was evaluated in relation to adsorbent dosage (30–330 mg/L), pH (4– 9) and mixing rate (100–350 rpm). Results showed that optimum dosage, pH and mixing rate for S. Potatorum were pH 8 with the dosage of 150 mg/L and 150 rpm mixing rate with the removal of turbidity, TSS, COD, O&G, and color are 91%, 97.6%, 58.4%, 79.9% and 84.3% respectively. Meanwhile, for P. Sativum, the optimum condition was observed at pH 8 with the dosage of 150 mg/L and 150 rpm mixing rate with the removal of turbidity, TSS, COD, O&G, and color 87.8%, 97.3%, 65.5%, 77.9% and 76.5% respectively. The Langmuir model was found to be the best fit (R2 > 0.95) for TSS, O&G and color removal from MFPW in both coagulants, compared to the Freundlich model for both natural coagulants. In contrast, the Freundlich isotherms were best described by the removal of turbidity (R2 = 0.97) and COD (R2 = 0.93) by using P. Sativum. The findings obtained showed that natural coagulants give an efficient treatment solution for improving MFPW quality.